Desarrollo del área cognitiva a través de herramientas tecnológicas en niños de 12 a 24 meses - Tobar Palma, Carla Dayana (2017)
The present research work, had as goal to relate children's learning theories, guiding exercises and the stimuli required during the cognitive area development using conventional and technological didactic material in order to improve mastery of achievement in children between 1 to 2 years old. The investigation problem takes into account the need to design a technological tool that allows to maximize the cognitive processes; senso-perception, attention, memory. For this the proposal is to design a didactic activities manual where it relates fundaments, theories and pedagogical methods. The activities recommended in the manual are performed with the help of a technological tool that provides specific exercises to develop the cognitive processes through the use of the senses; in the senso-perception it will work textures, smells, tastes that offers the child to be in contact with the environment, for the attention and the memory....